2022
DOI: 10.3389/fcvm.2022.984092
|View full text |Cite
|
Sign up to set email alerts
|

The effect of SGLT-2i administration on red blood cell distribution width in patients with heart failure and type 2 diabetes mellitus: A randomized study

Abstract: BackgroundRecent studies suggest that the pivotal mechanism of sodium glucose co-transporter-2 inhibitors (SGLT-2i) favorable action in patients with heart failure (HF) and type 2 diabetes mellitus (DM) is the stimulation of erythropoiesis via an early increase in erythropoietin (EPO) production which leads to hematocrit rise. Red blood cell distribution width (RDW) is a simple hematological parameter which reflects the heterogeneity of the red blood cell size (anisocytosis). Since, EPO has been also implicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…This finding indicated that an increased ΔRDW was associated with a high risk of all‐cause mortality, regardless of the presence of anaemia, and common co‐morbidities such as diabetes mellitus and coronary heart disease. This finding is in accordance with previous studies 12,38–41 . However, because HF is a complex syndrome caused by various heart diseases, the predictive value of the RDW for the prognosis could be different.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding indicated that an increased ΔRDW was associated with a high risk of all‐cause mortality, regardless of the presence of anaemia, and common co‐morbidities such as diabetes mellitus and coronary heart disease. This finding is in accordance with previous studies 12,38–41 . However, because HF is a complex syndrome caused by various heart diseases, the predictive value of the RDW for the prognosis could be different.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in accordance with previous studies. 12 , 38 , 39 , 40 , 41 However, because HF is a complex syndrome caused by various heart diseases, the predictive value of the RDW for the prognosis could be different. Zhang et al reported that the RDW was a prognostic indicator for patients with HF caused by coronary heart disease and dilated cardiomyopathy, but not valvular heart disease.…”
Section: Discussionmentioning
confidence: 99%